Insurance Among Young Adults With Inflammatory Bowel Disease: Changes Under the Affordable Care Act Dependent Provision. Issue 6 (June 2017) - Whitfield, Emily; Adler, Jeremy; Gebremariam, Acham; Davis, Matthew
ABSTRACT: Background: A total of 20% to 30% of patients with inflammatory bowel disease (IBD) present before age 18 years, eventually requiring transfer to adult care. Vulnerability during transfer may be exacerbated by loss of insurance. A provision of the Affordable Care Act (ACA) allows young adults (YAs) to remain on parental private insurance through age 25 years. There has been a decrease in uninsured YAs since its implementation in 2010. Little is known about whether insurance coverage of YAs with IBD has been affected. Objective: The aim of the present study was to determine whether the proportion of uninsured YAs with IBD has changed following the implementation of extended dependent eligibility under the ACA. Methods: We conducted a cross-sectional analysis of hospitalized patients with IBD, identified in the Nationwide Inpatient Sample (NIS) using diagnostic codes, to estimate proportions of insurance coverage during the years 2006–2013. We compared 19 to 25 year olds to 2 to 18 and 26 to 35 year olds, unaffected by the provision, to account for underlying trends. Results: From 2006 to 2010, 19 to 25 year olds had the highest proportion of uninsured, peaking at 14.1% in 2010. In 2011, the proportion decreased to 10.1%, below the proportion of uninsured 26 to 35 year olds (13.1%), remaining in this range through 2013. Private coverage increased in 2011 for 19 to 25 year olds, remaining stable for 26 to 35 year olds. Discussion: Previous research cited 5% uninsured among all hospitalized patients with IBD. Our study indicates a higher proportion for YAs, decreasing after the ACA. Lack of insurance increases vulnerability during transfer but may be modifiable through policy change. Furthermore, research should analyze the effects of Medicaid expansion and health care exchanges. Abstract : Supplemental Digital Content is available in the text